Intravitreal low-dose triamcinolone acetonide for nonarteritic anterior ischemic optic neuropathy - Zi-Jia Liu; Xian Xu; Ya-Nan Lyu; Dong-Li Li; Hao Zhou; Yuan-Yuan Gong (International Journal of Ophthalmology)
AIM: To evaluate the efficacy and safety of intravitreal low-dose (1 mg) triamcinolone acetonide (TA) in Chinese acute nonarteritic anterior ischemic optic neuropathy (NAION) patients. METHODS: Twenty-eight eyes of 28 patients with acute NAION (<30d of visual acuity loss) were enrolled and given intravitreal TA (IVTA) once. Visual field (VF), best corrected visual acuity (BCVA), retinal nerve fiber layer (RNFL) thickness, ganglion cell complex (GCC) thickness, radial peripapillary capillary (RPC) density, and intraocular pressure (IOP) were evaluated at baseline and 7d, 1, 3, and 6mo after IVTA. RESULTS: VF and BCVA were significant improved during the follow-up according to the mean deviation (MD), visual field index (VFI), and Early Treatment Diabetic Retinopathy Study (ETDRS) scores (all P<0.001). There was no significant difference between the group that received an injection less than 14d after illness onset and the group that received an injection more than 14d after illness onset. The RNFL thickness, GCC thickness and RPC density were significantly decreased (all P<0.001). Temporary ocular hypertension was present in five eyes. CONCLUSION: Low-dose IVTA may be an alternative safe treatment option for some NAION patients in the acute stage. However, optic nerve atrophy still existed.